Kamikihito improves cancer‐related fatigue in castration‐resistant prostate cancer patients receiving enzalutamide: Multidimensional approach including metabolomics analysis. Issue 3 (16th September 2021) - Tamada, Satoshi; Iguchi, Taro; Kato, Minoru; Yamasaki, Takeshi; Tsuchiya, Naoko; Ohbuchi, Katsuya; Shimobori, Chika; Nojima, Junzo; Yasuda, Sayaka; Ebisu, Kyoko; Watanabe, Yasuyoshi
ABSTRACT: Aim: We have previously reported the therapeutic benefits of kamikihito for managing cancer‐related fatigue (CRF) in patients with hormone‐sensitive prostate cancer. Now, due to the routine use of enzalutamide and similar agents for treating castration‐resistant prostate cancer (CRPC), managing enzalutamide‐related fatigue is imperative. Here, we objectively evaluated the effectiveness of kamikihito on fatigue in CRPC patients receiving enzalutamide. Methods: Kamikihito was administered for 12 weeks to 11 patients receiving enzalutamide. We measured the changes in the levels of fatigue (using the Chalder Fatigue Scale (CFS)), depression (using the Center for Epidemiologic Studies Depression Scale (CES‐D)), oxidative stress (by measuring derivatives of reactive oxygen metabolites (d‐ROMs) and biological antioxidant potential (BAP) levels), various cytokines, insomnia (using actigraphy), and in‐vivo metabolites (by metabolomics analysis). Results: Kamikihito improved CFS and CES‐D scores, thus improving fatigue and depression in enzalutamide‐treated patients; however, it did not improve oxidative stress levels. Further, actigraphy showed prolongation of sleeping time, while the levels of various cytokines showed no change. Metabolomics analysis confirmed decrease in lipids and increase in amino acids that correlated with improvement in fatigue. Conclusion: Kamikihito corrected the abnormalities in lipid metabolism, which may have improved the production of amino acids, leading to reduced CRF in CRPC patients receiving enzalutamide.